Integrating spatial transcriptomics with single-cell transcriptomics reveals a spatiotemporal gene landscape of the human developing kidney - Wu, Hongwei; Liu, Fanna; Shangguan, Yu; Yang, Yane; Shi, Wei; Hu, Wenlong; Zeng, Zhipeng; Hu, Nan; Zhang, Xinzhou; Hocher, Berthold; Tang, Donge; Yin, Lianghong; et al. (Cell & bioscience, 2022)
Research on spatiotemporal gene landscape can provide insights into the spatial characteristics of human kidney development and facilitate kidney organoid cultivation. Here, we profiled the spatiotemporal gene programs of the human embryonic kidneys at 9 and 18 post-conception weeks (PCW) by integrating the application of microarray-based spatial transcriptomics and single-cell transcriptomics. We mapped transcriptomic signatures of scRNA-seq cell types upon the 9 and 18 PCW kidney sections based on cell-type deconvolution and multimodal intersection analyses, depicting a spatial landscape of developing cell subpopulations. We established the gene characteristics in the medullary regions and revealed a strong mitochondrial oxidative phosphorylation and glycolysis activity in the deeper medullary region. We also built a regulatory network centered on GDNF-ETV4 for nephrogenic niche development based on the weighted gene co-expression network analysis and highlighted the key roles of Wnt, FGF, and JAG1-Notch2 signaling in maintaining renal branching morphogenesis. Our findings obtained by this spatiotemporal gene program are expected to improve the current understanding of kidney development.
Gesehen am 16.10.2023